PIV and IRT measurements of hydrothermal performance in a U-shaped heat exchanger with 3D printed detached curved ribs. (February 2023) - Wang, Chun-Sheng; Wang, En-Shuo; Huang, Yu-Jie; Liou, Tong-Miin
Highlights: Novel physics inspired ribs fabricated with 3D printing are firstly proposed. The effects of convergence/divergence angle and clearance ratio are revealed. Optimal values of convergence/divergence angle and clearance ratio are identified. Empirical correlations of N u ¯ / N u ∞ and f ¯ / f ∞ for the proposed ribs are formulated. Abstract: Novel detached curved ribs are proposed in this study and their influence on turbulent thermofluidic features in a two-pass U-shaped square channel is experimentally investigated using particle image velocimetry (PIV) and infrared thermography (IRT). Due to their geometric complexity, the ribs are fabricated with the 3D printing technology-fused deposition modeling and mounted in line inside the channel with a hydraulic diameter ( DH ) of 45.5 mm. Examined parameters include the rib convergence angle ( α ), divergence angle ( β ), clearance ratio ( C / H ), and Reynolds number, which are respectively in the range of (25°, 35°, 45°), (30°, 40°, 50°), (0.25, 0.38, 0.56, 0.75, and 1), and (5, 000–20, 000). The PIV and IRT results show that that the detached curved ribs accelerate the core flow and significantly strengthen the Dean vortices in the turn region, leading up to 70% enhancement in Nusselt number ratio ( N u ¯ / N u ∞ ) in that region compared with previous best results. Further parametric studies reveal that at α =25˚and β  = 40°, N u ¯ / N u ∞ and Fanning friction factor ratio ( f ¯ / f ∞ ) first increase and then decrease with increasing C / H, with the maximum thermal performance factor ( TPF ) of 1.4 occurring at C / H  = 0.38, slightly higher than the previous highest data for f ¯ / f ∞ = 10-50. Finally, empirical formulations of N u ¯ / N u ∞ and f ¯ / f ∞ with α, β, C/H, and Re for the present design are proposed with an average difference of 2.24% and 4.95%, respectively.